Impact of foreign ownership on dividend policy in Poland - Andrzej Zyguła (e-Finanse: Financial Internet Quarterly, 2017)
The article analyses the impact of foreign investors, who were the majority shareholders of companies on the Warsaw Stock Exchange, on dividend policy of these companies in the years 2004-2014. An evaluation of the direction and strength of the influence of the analysed group of investors, using 2 models, was conducted applying logistic regression. The first - dividend payout policy based on the binary logit model - showed that along with a growing share of a foreign investor in a given company the probability of dividend payment by the company increased significantly. The second - dividend level change model based on the multinominal logit method - showed, however, that with an increasing share of foreign investors the probability that a given company will reduce the paid dividend level was enhanced significantly. Additionally, it should be stated that these results, irrespective of the model used, were to a very large extent in line with conclusions of the pecking order theory. However, in the case of signaling, free cash flow and maturity theories, these results only to a small extent provided evidence supporting these theories.
Keywords: G32; G35; 330; ownership structure; dividends; foreign investors; payout policy